Stress levels, stressors, and coping strategies among nursing students during maternal and child health clinical rotations: A cross-sectional study in Saudi Arabia - Abdelmaksoud, Amaal Samir; Fadila, Doaa El Sayed; Alhumaidi, Bandar Naffaa; Al-Sayaghi, Khaled Mohammed; Roque, Mark Yuga; Relloso, Joyce Toriente; Fadlalmola, Hammad Ali (Belitung Raya Publisher - Belitung Raya Foundation, 2026)
Background: Nursing students often experience high levels of stress during clinical training, particularly in maternal and child health (MCH) rotations, which may affect learning and well-being. Understanding stress levels, stressors, and coping strategies can inform the development of supportive and culturally appropriate educational approaches. Objective: To assess perceived stress levels, identify clinical stressors, and examine coping strategies among nursing students during MCH clinical rotations in Saudi Arabia. Methods: A cross-sectional study was conducted in 2024 among 187 female nursing students enrolled in MCH clinical rotations. Data were collected using validated Arabic versions of the Perceived Stress Scale (PSS-10), the Nursing Student Clinical Stressor Scale (NSCSS), and the Brief COPE Inventory. Descriptive statistics and Spearman’s rho correlation analyses were performed using SPSS. Results: Most students reported moderate perceived stress (75.4%), with a mean PSS-10 score of 20.5 ± 5.9. The highest stressor domains were MCH-specific challenges (9.13 ± 5.00), academic pressures (8.72 ± 3.95), and the clinical environment (7.65 ± 3.64). Religion (5.20 ± 2.06) and acceptance (4.79 ± 1.80) had the highest mean scores among coping strategies, while substance use was least reported (3.04 ± 1.40). Self-blame showed the strongest association with total clinical stressors (rho = 0.501, p <0.001). Conclusion: Female nursing students experienced moderate stress during MCH clinical rotations, largely related to clinical and academic demands. Coping strategies were predominantly emotion-focused, with self-blame showing a strong association with higher stress levels. These findings highlight the importance of culturally sensitive support strategies in nursing education.